Penerapan Model Pembelajaran Cooperative Integrated Reading and Compocition (CIRC) untuk Meningkatkan Hasil Belajar Biologi - Wakang, Anisa; Tuaputty, Hasan; Bahalwan, Farida (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2021)
Understanding and student learning outcomes have become a major problem in education today. There are various learning models that can be used by teachers, including the Cooperative Integrated Reading and Compocition (CIRC) learning model. This study aims to determine the application of the CIRC learning model in improving Biology learning outcomes. The type of research used in this study was descriptive quantitative with a sample of 29 students. The sampling technique uses cluster random sampling. The instruments of this study are observations and tests. Observation guidelines are carried out to determine the objective learning conditions carried out by teachers and students. The test used in this study is in the form of student learning results obtained in the implementation of the test. The results showed that the application of the CIRC learning model can improve student learning outcomes.